Evaluation of the vegetation index and the concentration of metals in sediments in the Tarumã Microbasin, Mato Grosso do Sul, Brazil (Research, Society and Development, 2020)
The aim of the study was to evaluate quantitative physical-chemical parameters of water from streams in the Tarumã microbasin (MS, Brazil), to quantify metals (Cd, Pb, Cr, Cu, Fe, Zn and Ni) in the bottom sediments of these streams and to evaluate quali-quantitatively the vegetation index of normalized difference of locations (NDVI) by means of satellite images.Water turbidity and electrical conductivity values were highest at the nearest points in the urban region. In the NDVI analysis, sites P1, P2 and P4 presented reduced local ciliary vegetation, classified as low or very low. At sites P3, P5 and P6 we found higher proportions of vegetation at moderate and low levels. Regarding metals in sediments, all sampled sites presented metal concentrations below the limits established by current legislation. The low rate of vegetation cover around streams in the Tarumã microbasin, especially in spring sites, may compromise the equilibrium of this system.